Analisis Pola Perbaikan Ujaran (Repair Strategies) dalam Interaksi Kelas Bahasa Indonesia sebagai Bahasa Kedua di YouTube - Wulandari, Nadia Putri; Mujianto, Gigit; Setiawan, Arif (Edukasi Lingua Sastra, 2026)
Oral interaction plays a crucial role in second language learning, particularly in Bahasa Indonesia for Foreign Speakers (BIPA), where meaning negotiation and utterance repair frequently occur during classroom communication. In the context of digital learning, platforms such as YouTube provide authentic interactional settings that allow teachers and learners to engage in real-time corrective practices. This study aims to identify the types of repair initiation, analyze the repair strategies employed, and explain the pedagogical functions of repair in BIPA learning through YouTube-based instructional videos. Using a qualitative descriptive approach, the data were obtained from two BIPA learning videos uploaded on YouTube and analyzed through conversation-based interactional analysis. The findings reveal two types of repair initiation: self-initiation and other-initiation, with other-initiation occurring more frequently, indicating the dominant role of teachers in guiding beginner learners. The repair strategies identified include repetition, reformulation, and substitution, with repetition emerging as the most dominant strategy due to its effectiveness in supporting immediate correction and reinforcing accurate language forms. Furthermore, repair practices were found to serve significant pedagogical functions, such as clarifying meaning, providing accurate linguistic models, fostering learner confidence, and promoting metalinguistic awareness. The study also demonstrates that digital learning media facilitate flexible and collaborative repair processes, enabling learners to revisit input and engage more actively in self-correction. Overall, this research highlights that repair is not merely a corrective mechanism but an integral pedagogical strategy that supports the development of speaking skills and interactional competence in digital BIPA classrooms.